2021
DOI: 10.1007/s11258-021-01126-4
|View full text |Cite
|
Sign up to set email alerts
|

Friend or foe? The role of biotic agents in drought-induced plant mortality

Abstract: Plant mortality is a complex process influenced by both biotic and abiotic factors. In recent decades, widespread mortality events have been attributed to increasing drought severity, which has motivated research to examine the physiological mechanisms of drought-induced mortality, particularly hydraulic failure. Drought-based mortality mechanisms are further influenced by plant interactions with biota such as neighboring plants, insect pests, and microbes. In this review, we highlight some of the most influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…We show that plant-plant interactions create an additional source of variation in plant dehydration tolerance (χ² = 8.87, p = 0.0118, Table 1) that has been rarely tested previously (Griffin-Nolan et al, 2021). As expected, we found opposite responses between the two species, suggesting a positive relationship between plant dehydration tolerance and benefits from biodiversity effects in mixtures.…”
Section: Dehydration Tolerance and Post-drought Recovery Vary With Pl...supporting
confidence: 72%
See 2 more Smart Citations
“…We show that plant-plant interactions create an additional source of variation in plant dehydration tolerance (χ² = 8.87, p = 0.0118, Table 1) that has been rarely tested previously (Griffin-Nolan et al, 2021). As expected, we found opposite responses between the two species, suggesting a positive relationship between plant dehydration tolerance and benefits from biodiversity effects in mixtures.…”
Section: Dehydration Tolerance and Post-drought Recovery Vary With Pl...supporting
confidence: 72%
“…Despite changes in plant density, we support that plant diversity improves the resilience capacity to drought in grass mixtures (Tilman & Downing, 1994), as found in forests (Grossiord et al, 2014; Hisano et al, 2019). This effect could be even higher when complementary drought strategies are associated together and allow recovering productivity after drought (Wright et al, 2021), for example, in natura where F. arundinacea can efficiently better ‘avoid’ dehydration by capturing water from deep soil layers, reducing interspecific competition and maximizing ecosystem functioning (Godoy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McDowell et al, 2008McDowell et al, , 2022Peltier et al, 2023), much less is known about mortality mechanisms in herbaceous-dominated ecosystems (e.g. Griffin-Nolan et al, 2021;Niu et al, 2014;Norton et al, 2016). This is a critical knowledge inequity because herbaceous-dominated ecosystems may equal or exceed the global land cover of forests.…”
Section: Looking Forwardmentioning
confidence: 99%
“…Similar to results gained from most drought intensity experiments with trees (Li et al, 2013;Schönbeck et al, 2018Schönbeck et al, , 2020aZhang et al, 2020;Ouyang et al, 2021), the present study found that the longer drought duration treatments (D2, D3) did not decrease the end-season leaf NSC (pre-winter) levels (Figures 3A,F), although the D2 and D3 treatment significantly decreased leaf photosynthesis of the two species (Figures 2C-F). This might be explained by the osmoregulation strategy of plants suffering from drought stress on the one hand (O'Brien et al, 2014;Dickman et al, 2015), and on the other hand, it may be a result of basipetal carbon translocation failure (Rowland et al, 2015), if the phloem function becomes impaired and carbon translocation gets limited or stopped by hydraulic failure caused by severe or long drought stress (Griffin-Nolan et al, 2021). In this case, lower NSC levels in the sink tissues of shoots, and especially roots, and thus carbon limitation may be expected.…”
Section: Schönbeckmentioning
confidence: 99%